Residency of the whitetip reef shark (Triaenodon obesus) in Chatham and Wafer Bays, Isla del Coco National Park, Costa Rica. - López-Garro, Andrés; Zanella, Ilena; Golfín-Duarte, Geiner; Pérez-Montero, Maikel (Revista de Biología Tropical, 2020)
Introduction: The whitetip reef shark (Triaenodon obesus) is a non-migratory tropical reef species that has shown no high coastal connectivity, as observed for other shark species. At the same time, has the widest distribution of all Indo-Pacific reef shark species. Triaenodon obesus is one of the most common shark species at Isla del Coco National Park (PNIC) and it is present year-round. In the bays located in the north of the PNIC, Chatham Bay and Wafer Bay, there is a large population of whitetip reef sharks. Despite that, information about its residency is scarce. Objective: The aim of this initiative is to study the hábitat use and the movements of the whitetip reef sharks, in order to improve the management of its population at the Isla del Coco National Park and other áreas of Eastern Tropical Pacific. A preliminary study on the residency in the Chatham and Wafer bays of the PNIC was conducted, using acoustic telemetry. Methods: A shark tagging expedition was made to Isla del Coco National Park from November 25 to December 5, 2014. During this expedition, two night trips were made between 6:00 pm and 10:00 pm at Chatham Bay and Wafer Bay. Results: A total of 8 individuals of T. obesus were fitted with acoustic tags and two receivers were installed, one in each bay. Sharks were monitored between November 2014 and December 2015, the sharks were detected on 278 706 occasions. The sharks remained long periods in the Chatham and Wafer bays. Their average Residency Index (IR) was 0.97 ± 0.03, reporting less number of detections during the night hours. Detections of sharks in the bays tend to diminish after 18:00, when the whitetip shark becomes active to hunt on the reef. Conclusions: In conclusion, white tip sharks have a high residence and fidelity, which confirms their low home range. The Protected Marine Area of Isla del Coco probably provides effective protection to the white tip shark population for the illegal fisheries.